(NpATOLOGI^ESKAQ ANATOMIQ (B2-(N^ASTXs (NU^EBNIK s - (Nm(B.(Ns(B.(NaBDULLAHODVAEWA s; (Nr(B.(Ni(B.(NiSRAILOW s; (Nz(B.(Ng(B.(NtUHWATULLINA s ((NtA[KENT s "Tafakkur-bo'stoni", 2012)
II (N^ASTI POSWQ[ENA PATOLOGI^ESKOJ ANATOMII BOLEZNEJ(B,(NIZLOVENNOJ PO NOZOLOGI^ESKOMU PRIN[IPU (B((NORGONOPATOLOGIQ (B).s
Keywords: (NpATOLOGI^ESKAQ ANATOMIQ (B2-(N^ASTs